The Cambridge Introduction to Walter Benjamin - Ferris, David S (Cambridge University Press, 2013)
Topresent theworkofWalterBenjamin in the formof an introduction requires a willingness to face the challenge posed by a body of work recognized for its range and the difficulty of its concepts, as well as this critic’s recursive and frequently elliptical writing style